INDOMOD A Simulation Model of the Indonesian Economy. (IMF Working Papers; Working Paper ;, 1989)
This paper presents a small macro simulation model of the Indonesian economy The model was constructed to assess the effects of alternative policies as well as changes in the external environment on the Indonesian economy over the medium term Accordingly, the focus is on the determinants of growth with relatively little attention devoted to explaining the effects of short-run demand fluctuations.